Interpretation and Indigenous Wisdom - Ismail Martono; Mursalim; Muryani (Bulletin of Pedagogical Research, 2025)
This study examines the concept of local-wisdom Qur’anic exegesis as an interpretive approach that integrates the Qur’anic message with the language, values, and cultural symbols of Nusantara communities. Using a qualitative library-research method, this study traces the development of local-wisdom tafsir from the interpretive practices of Prophet Muhammad ﷺ, the spread of Islam across various regions, to its consolidation in the Nusantara through dakwah and local-language manuscripts. The findings show that this approach facilitates public understanding, strengthens the cultural identity of Islam Nusantara, and serves as an effective medium for religious communication. Nevertheless, it also presents limitations, including the potential dominance of cultural elements over the text and the need for interpreters to possess competence in both cultural knowledge and Qur’anic sciences. This study affirms that local-wisdom tafsir is an essential approach for contextualizing the Qur’an in multicultural societies.